MODERN POTENTIALITIES OF IMMUNOPROPHYLAXIS OF SEVERE COURSE OF THE RESPIRATORY SYNCYTIAL VIRAL INFECTION IN CHILDREN WITH THE CONSEQUENCES OF PERINATAL PATHOLOGY - L.S. Namazova-Baranova; I.V. Davydova; T.V. Turti; I.A. Belyaeva; V.V. Altunin (Union of pediatricians of Russia, 2011)
To a risk group of a heavy course of the respiratory syncytial viral (RSV) infection could be ascribed preterm infants, born before the 35th week of gestation inclusive, as well as children under 2 years old with the bronchopulmonary dysplasia or hemodynamically significant congenital heart defects. World experience shows that the seasonal immunoprophylaxis against RSV-infection with palivizumab in these patients enables to reduce the frequency of hospitalization and resuscitation measures, as well as to decrease the number of deaths. The article presents authors' clinical and laboratory data and instrumental evaluation of the efficacy and safety of palivizumab on specific clinical examples.Key words: respiratory syncytial virus, acute respiratory viral infection, prematurity, bronchopulmonary dysplasia, congenital heart defects, palivizumab.